Post‐prophylaxis Toxoplasma chorioretinitis following donor–recipient mismatched liver transplantation. Issue 5 (October 2016) - Webb, G.J.; Shah, H.; David, M.D.; Tiew, S.; Beare, N.; Hirschfield, G.M.
Abstract: Toxoplasmosis may be transferred by organ transplantation. The most common clinical presentation is with multisystem disease, although isolated ocular toxoplasmosis has been described. Many centers have suggested that universal use of co‐trimoxazole prophylaxis obviates the need for specific Toxoplasma testing. We report a case of donor‐acquired ocular toxoplasmosis after liver transplantation despite co‐trimoxazole prophylaxis. The diagnosis was confirmed by Toxoplasma polymerase chain reaction assay in conjunction with seroconversion. The fact that the infection was donor acquired was confirmed by serological mismatch and the absence of sporozoite‐specific antigen antibody in the recipient.